The influence of social identity when digitally sharing location - Rahman, Abdur (2016)
By enabling users to self-report their whereabouts and share it with a vast and diverse audience, location sharing systems can be useful means of projecting the self and expressing one’s social identity (an individual’s personal self-conception). Through three research studies, this thesis investigates how social identity influences the digital sharing of location. It does so by first exploring how people socially interact offline and then investigates how facets of this behaviour are enacted in location sharing systems. Thus, it offers insights into how offline social behaviour extends to digital spaces and how it impacts social interaction in the digital realm.